Identification of Extracellular Matrix Signatures as Novel Potential Prognostic Biomarkers in Lung Adenocarcinoma - Zeng, Zhen; Zuo, Yuanli; Jin, Yang; Peng, Yong; Zhu, Xiaofeng (Frontiers in Genetics, 2022)
The extracellular matrix (ECM) is vital to normal cellular function and has emerged as a key factor in cancer initiation and metastasis. However, the prognostic and oncological values of ECM organization-related genes have not been comprehensively explored in lung adenocarcinoma (LUAD) patients. In this study, we included LUAD samples from The Cancer Genome Atlas (TCGA, training set) and other three validation sets (GSE87340, GSE140343 and GSE115002), then we constructed a three-gene prognostic signature based on ECM organization-related genes using Cox regression with least absolute shrinkage and selection operator (LASSO) penalty. The prognostic signature involving COL4A6, FGA and FSCN1 was powerful and robust in both the training and validation datasets. We further constructed a composite prognostic nomogram to facilitate clinical practice by integrating an ECM organization-related signature with clinical characteristics, including age and TNM stage. Patients with higher risk scores were characterized by proliferation, metastasis and immune hallmarks. It’s worth noting that high-risk group showed higher fibroblast infiltration in tumor tissue. Accordingly, factors (IGFBP5, CLCF1 and IL6) secreted by cancer-associated fibroblasts (CAFs) showed higher expression level in the high-risk group. Our findings highlight the prognostic value of the ECM organization signature in LUAD and provide insights into the specific clinical and molecular features underlying the ECM organization-related signature, which may be important for patient treatment.